2002
DOI: 10.1023/a:1016415805637
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Patients receiving home total parenteral nutrition (HTPN) are at risk for the development of essential fatty acid deficiency (EFAD). This study examined the essential fatty acid status of patients on long-term HTPN for gut failure. Serum phospholipid and triglyceride fatty acids were measured in 11 patients and 10 healthy volunteers. Patients had similar levels of linoleic acid (18:2w6) in serum triglyceride fatty acids but significantly lower levels of 18:2w6 in serum phospholipids compared to controls. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Mead acid is less abundant in cholesterol esters and the non-esterified lipid fraction [ 16 ]. Studies assessing EFAD have shown no significant difference when assessing Mead acid in either phospholipids or triglycerides [ 15 ]. The dried blood spot method utilized in the current study analyzes whole blood samples in which the FA proportions are roughly derived 50:50 from red blood cells and plasma [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mead acid is less abundant in cholesterol esters and the non-esterified lipid fraction [ 16 ]. Studies assessing EFAD have shown no significant difference when assessing Mead acid in either phospholipids or triglycerides [ 15 ]. The dried blood spot method utilized in the current study analyzes whole blood samples in which the FA proportions are roughly derived 50:50 from red blood cells and plasma [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in situations where individuals do not consume sufficient amounts of the EFAs, the non-essential n-9 FA oleic acid (C18:1n9) is converted to Mead acid (C20:3n9) [ 14 ]. Mead acid is incorporated in phospholipids, cholesterol esters, and triglycerides, as well as being found as a non-esterified free FA [ 15 , 16 ]. EFA deficiency (EFAD) leads to higher levels of Mead acid and an elevated triene to tetraene ratio (the T/T ratio), which is defined as the ratio of Mead acid to arachidonic acid (ARA) [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, when an individual’s diet is deficient of EFAs, oleic acid (C18:1n9), a non-essential n-9 FA, is converted to Mead acid (C20:3n9) [ 12 ]. Mead acid is then incorporated into phospholipids, cholesterol esters, triglycerides and non-esterified free FAs [ 13 , 14 ]. Therefore, in EFA deficiency, there are elevated levels of Mead acid with a decrease in the production of other EFA metabolites such as AA.…”
Section: Introductionmentioning
confidence: 99%